2019
DOI: 10.1021/acs.est.8b06380
|View full text |Cite
|
Sign up to set email alerts
|

Uranium Uptake in Paracentrotus lividus Sea Urchin, Accumulation and Speciation

Abstract: Uranium speciation and bioaccumulation were investigated in the sea urchin Paracentrotus lividus. Through accumulation experiments in a well-controlled aquarium followed by ICP-OES analysis, the quantification of uranium in the different compartments of the sea urchin was performed. Uranium is mainly distributed in the test (skeletal components), as it is the major constituent of the sea urchin, but in terms of quantity of uranium per gram of compartment, the following rating: intestinal tract > gonads >> test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…As expected, Co is not evenly distributed in the specimen. The ranking (intestinal tract ≫ gonads > test (shell + spines)) is in agreement with that reported for most heavy metals by Warnau et al and also coherent with previous results obtained with uranium . Only SU1a shows a different trend and 60 Co amounts in the intestinal tract of the same order as that in the gonads.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, Co is not evenly distributed in the specimen. The ranking (intestinal tract ≫ gonads > test (shell + spines)) is in agreement with that reported for most heavy metals by Warnau et al and also coherent with previous results obtained with uranium . Only SU1a shows a different trend and 60 Co amounts in the intestinal tract of the same order as that in the gonads.…”
Section: Resultssupporting
confidence: 92%
“…Previous investigations on the speciation and mechanisms of metallic radionuclide accumulation in the marine system by P. lividus have been recently performed with uranium using extended X-ray absorption fine structure (EXAFS) and time-resolved laser-induced fluorescence (TRLIF) showing, in particular, the possibility of extrapolating the results toward the lowest limits of concentration. , …”
Section: Introductionmentioning
confidence: 99%
“…For Nat U, for instance, and using XAS spectroscopy, we provided evidence of the metabolization of uranium (under its most stable uranyl UO 2 2 + chemical form) in living P. lividus. [50] Furthermore, contaminated gonads of P. lividus were analyzed by Scanning Transmission X-ray Microscopy (STXM), a technique that couples XAS and microscopy in order to localize the element of interest in a 2-D space and define its speciation at the same time. Such a technique is suitable for element-selective imaging studies with a spatial resolution down to a few tens of nm.…”
Section: Speciation Of Radionuclides Transfer To Living Speciesmentioning
confidence: 99%
“…We investigated the chemical mechanisms of MTR ( Nat U, 60 Co, 137 Cs) uptake by P. lividus using a well‐controlled system of aquaria doped with the MTR of interest. For Nat U, for instance, and using XAS spectroscopy, we provided evidence of the metabolization of uranium (under its most stable uranyl UO 2 2+ chemical form) in living P. lividus [50] . Furthermore, contaminated gonads of P. lividus were analyzed by Scanning Transmission X‐ray Microscopy (STXM), a technique that couples XAS and microscopy in order to localize the element of interest in a 2‐D space and define its speciation at the same time.…”
Section: Introductionmentioning
confidence: 98%
“…33 A study of uranium speciation in sea urchins identified the uptake of uranium in the form of ternary calcium carbonato species. 34 Although ternary complexation is very striking with respect to the common fate of uranium under various environmental conditions, it has not been reported for hexavalent actinides other than U(VI).…”
Section: mentioning
confidence: 99%